How to attract them and keep them: the pharmacy attributes that matter to Australian residents with chronic conditions. (18th October 2013) - McMillan, Sara S; Sav, Adem; Kelly, Fiona; King, Michelle A; Whitty, Jennifer A; Wheeler, Amanda J
Abstract: Objective: To explore the attributes of pharmacy choice for people with chronic conditions. Methods: Semi-structured interviews were conducted between May and October 2012, across four regions in three Australian states. Purposive sampling was used to recruit participants with chronic conditions and unpaid carers. Interviews were analysed via the constant comparison method. Key findings: Ninety-seven interviews were conducted. The majority of participants were regular patrons of one pharmacy and five attributes influenced this choice: patient-centred care, convenience, price, personal trait or preference and service/medication need. Patient-centred care, such as providing individualised medication counselling, continuity of care, development of relationships and respectful advice, emerged as an important attribute. There was minimal discussion as to choosing a pharmacy based on the provision of professional services, underscoring the limited consumer knowledge of such services and related standards of care. Conclusion: Patient-centred care is an important attribute of quality care as perceived by people who are regular community pharmacy users. These findings highlight the need for pharmacy staff to implement a patient-centred approach to care, thus meeting the perceived needs of their customers. A greater effort is also necessary to raise the profile of pharmacy as a healthcare destination.